Taxation Digitalization Transformation: Taxpayer Perceptions of the E-System on the Quality of Tax Services - Mujiarti, Mujiarti; Amir, Amir; Santoso, Suryo Budi; Setyadi, Edi Joko (International Journal of Business and Applied Economics, 2025)
This research aims to explain the transformation of tax digitalization: taxpayers' perceptions of the e-system on the quality of tax services. This research is motivated by developments in service systems using internet technology. The method used in this research is quantitative. The data source was obtained from primary data by distributing questionnaires as research instrument material. Sampling was carried out using the purposive sampling method. The number of samples required for this research is 140 respondents who are individual and Corporate Taxpayers at KPP Pratama Purbalingga. The data analysis technique used in the research is Partial Least Square (PLS). Based on the results of the analysis carried out, it was concluded that the taxpayer perception of the e-registration and e-invoicing system has an influence on the quality of tax services, while the taxpayer perception of the e-filing and e-billing system has no influence on the quality of tax services.